Results of upper airway radiography and ultrasonography predict dynamic laryngeal collapse in affected horses. (23rd May 2013) - Fjordbakk, C. T.; Chalmers, H. J.; Holcombe, S. J.; Strand, E.
Summary Reasons for performing study The pathogenesis of dynamic bilateral laryngeal collapse (DLC) associated with poll flexion is unknown. Diagnosis is dependent upon exercise endoscopy while replicating the flexed head position harness racehorses experience during racing. Objectives To describe the effects of poll flexion on rostrocaudal laryngeal positioning and laryngeal lumen width in resting horses diagnosed with DLC compared to controls, and to establish diagnostic criteria for DLC by use of diagnostic imaging. Study design Case‐control study. Methods Fifty harness racehorses were prospectively included in the study: 25 cases diagnosed with DLC by treadmill endoscopy and 25 controls in which treadmill endoscopy revealed no abnormal findings. Laryngeal radiography and ultrasonography were obtained in neutral and flexed head positions. Laryngeal positioning and laryngohyoid conformation were compared between the groups and head positions. Results Poll flexion induced a greater rostral advancement of the larynx in relation to the hyoid apparatus in resting harness racehorses affected with DLC compared to controls (P = 0.007). At the level of the vocal folds, poll flexion resulted in a smaller laryngeal lumen width in horses affected with DLC compared to controls (P = 0.04). Horses were significantly more likely to be affected with DLC when the thyrohyoid bone to thyroid cartilage distance was ≥12 mm in poll flexion (odds ratio 21.3, 95% confidence interval 3.65–124.8, P = 0.004) and when laryngeal lumen width at the level of the vocal folds was less in poll flexion than in the neutral head position (odds ratio 8.4; 95% confidence interval 1.6–44.1, P = 0.012). Conclusions and potential relevance In DLC horses, poll flexion advanced the larynx more rostrally and resulted in a decreased airway lumen width compared to control horses. Laryngeal ultrasound and radiography may facilitate the diagnosis of DLC at rest.